HUBUNGAN ANTARA CAREGIVER BURDEN DENGAN SUBJECTIVE WELL-BEING PADA IBU GENERASI SANDWICH - Indira Khairunnisa; Nurul Hartini (Lafadz Jaya Publisher, 2022)
Caring and providing financial support for two generations in one family is inseparable from declining psychological aspects, one of which is subjective well-being that affected from caregiver burden. It is important for sandwich generation who bear multiple demands, to maintain their subjective well-being in a good quality . Pearson’s correlation analysis was conducted in 81 sandwich generation mothers that leads to result of a significant negative correlation between caregiver burden and subjective well-being (r= -0,539; p < 0,05). This result explains that if the level of caregiver burden is increased, the it decreases the subjective well-being level.